ANALYSE DE LA MEDIATION DANS LA RECHERCHE EN MANAGEMENT : L’IMPACT DE LA VEILLE DANS LA POSITION CONCURRENTIELLE DES PME - BADAOUI MOHAMED; CHETTIH ABDELKADER (Revue Marocaine de Recherche en Management et Marketing, 2020)
This study discusses a new method of analyzing mediation in a PLS context. It facilitates the adoption of new PLS procedures, by challenging the traditional approach of analyzing mediation by proposing more specific alternatives. In addition, the purpose of this article is to verify the existence of a role of the survey in the competitive position of SME. The study found the significance of the indirect effect of mediation.The survey confirmed the effect of influence as a mediator, there is a partial mediation of the relationship between the watch and the competitive position.This study discusses the state-of-the-art use of mediation analysis in the context of PLS.Findings —this study facilitates the adoption of modern procedures in PLS by challenging the conventional approach to mediation analysis and providing alternatives that are more accurate. In addition, the objective of this research paper is to verify the existence or not of a role of this discipline that is Foresight in the competitive position of SMEs. The study found the significance of indirect effect. On size of mediation, the survey confirmed Influence as a mediator, Partial mediating the relationship between Foresight and competitive position. The study found the significance of the indirect effect of mediation